Synthesis of magnetic cytosine-imprinted chitosan nanoparticles. (19th January 2017) - Lee, Mei-Hwa; Ahluwalia, Arti; Chen, Jian-Zhou; Shih, Neng-Lang; Lin, Hung-Yin
Abstract: Molecularly imprinted polymer nanoparticles incorporating magnetic nanoparticles (MNPs) have been investigated for their selective adsorption properties. Here we describe the synthesis and characterization of magnetic cytosine-imprinted chitosan nanoparticles (CIPs) for gene delivery. In particular, CIPs carrying the mammalian expression plasmid of enhanced green fluorescent protein were prepared by the co-precipitation of MNPs, chitosan and a template nucleobase (cytosine). The results show that the selective reabsorption of cytosine to magnetic CIPs was at least double that of non-imprinted polymers and other nucleobases (such as adenine and thymine). The gene carrier CIPs were used for the transfection of human embryonic kidney 293 cells showing dramatic increase their efficiency with that of conventional chitosan nanoparticles. Furthermore, the gene carrier magnetic CIPs also exhibit low toxicity compared to that of commercially available cationic lipids.